Respuesta :
Answer:
11) x=1 or x=3.
12) x=2/3 or x=-7.
Step-by-step explanation:
So we have two equations:
[tex]f(x)=3x(2x-6)\\f(x)=3x(x+7)-2(x+7)[/tex]
And we want to solve them. To do so, make each of them equal 0 and then solve for x:
11)
[tex]f(x)=3x(2x-6)\\0=3x(2x-6)[/tex]
Using the Zero Product Property, either one or both of the factor must be zero for this to be true. Therefore, make each factor equal to zero and solve:
[tex]3x=0 \text{ or } 2x-6=0[/tex]
Divide the left by 3. On the right, add 6 and then divide by 2:
[tex]x=0\text{ or } 2x=6\\x=0 \text{ or } x=3[/tex]
Therefore, the solutions to the first equation is:
x=1 or x=3.
12)
[tex]f(x)=3x(x+7)-2(x+7)[/tex]
First, use the distributive property to group the terms together. The equation is equivalent to:
[tex]f(x)=(3x-2)(x+7)[/tex]
Now, set the function to zero and solve:
[tex]0=(3x-2)(x+7)[/tex]
[tex](3x-2)=0 \text{ or } x+7=0\\3x=2 \text{ or } x=-7\\x=2/3 \text{ or } x=-7.[/tex]
Therefore, the answer is:
x=2/3 or x=-7.
Answer:
[tex]\large \boxed{{\bold{11.} \ x=0, \ x=3}} \\ \\ \large \boxed{{\bold{12.} \ x=-7, \ x=2/3}}[/tex]
Step-by-step explanation:
We will set the outputs of the functions to 0 and solve for x.
0 = 3x(2x - 6)
Set factors equal to 0.
First possibility:
3x = 0
x = 0
Second possibility:
2x - 6 = 0
2x = 6
x = 3
0=3x(x+7)-2(x+7)
Take (x+7) as a common factor.
0 = (3x-2)(x+7)
Set factors equal to 0.
First possibility:
x + 7 = 0
x = -7
Second possibility:
3x - 2 = 0
3x = 2
x = 2/3